DA LUTA POR DIREITOS AO EMPODERAMENTO FEMININO: OS ENTRAVES PARA O COMBATE À DESIGUALDADE DE GÊNERO NO BRASIL - Rosane Cristina Oliveira; Raphael Fernandes Gomes; Jacqueline de Cássia Pinheiro Lima (TRF2, 2018)
The purpose of this article is to present a discussion on women's rights and women's empowerment, reflecting on the obstacles to the fight against gender inequality in Brazilian society. Although advances in the achievement of women's rights are important, this study emphasizes that in contexts of advancement of conservative thinking and the difficulty in dismantling certain elements typical of culture and of discriminatory and patriarchal behaviors, ther are obstacles that promote morosity in the fight against gender inequality in Brazil. Theoretically, the study is based on the feminist authors Simone de Beauvoir, Judith Butler, Heleieth Saffioti, Srilatha Batliwala, among others. From a methodological point of view, this work was based on bibliographic, exploratory and documentary research.